Relational and algebraic methods in computer science 12th International Conference, RAMICS 2011, Rotterdam, The Netherlands, May 30 - June 3, 2011. Proceedings - de Swart, Harrie (Lecture notes in computer science, 2011)
This book constitutes the proceedings of the 12 International Conference on Relational and Algebraic Methods in Computer Science, RAMICS 2011, held in Rotterdam, The Netherlands, in May/June 2011. This conference merges the RelMICS (Relational Methods in Computer Science) and AKA (Applications of Kleene Algebra) conferences, which have been a main forum for researchers who use the calculus of relations and similar algebraic formalisms as methodological and conceptual tools.  Relational and algebraic methods and software tools turn out to be useful for solving problems in social choice and game theory. For that reason this conference included a special track on Computational Social Choice and Social Software. The 18 papers included were carefully reviewed and selected from 27 submissions. In addition the volume contains 2 invited tutorials and 5 invited talks.